Plasma exchange therapy in HELLP syndrome: A single-center experience - Ziya BAYRAKTAROĞLU; Fikret DEMİRCİ; Özcan BALAT; İrfan KUTLAR; Vahap OKAN; Gürol UĞUR (Turkish Journal of Gastroenterology, 2019)
-